Comparative Phenotypic and Genomic Features of Staphylococci from Sonication Fluid of Orthopedic Implant-Associated Infections with Poor Outcome - Ingrid Nayara Marcelino Santos; Mariana Neri Lucas Kurihara; Fernanda Fernandes Santos; Tiago Barcelos Valiatti; Juliana Thalita Paulino da Silva; Antônio Carlos Campos Pignatari; Mauro José Salles (Microorganisms, 2022)
Staphylococcus spp. remain the leading biofilm-forming agents causing orthopedic implant-associated infections (OIAI). This is a descriptive study of phenotypic and genomic features identified in clinical isolates of S. aureus and coagulase-negative Staphylococcus (CoNS) recovered from OIAIs patients that progressed to treatment failure. Ten isolates were identified by matrix-time-of-flight laser-assisted desorption mass spectrometry (MALDI-TOF-MS) and tested for antibiotic susceptibility and biofilm formation. Genotypic characteristics, including, MLST (Multi Locus Sequence Typing), SCCmec typing, virulence and resistance genes were assessed by whole-genome sequencing (WGS). All S. aureus harbored mecA, blaZ, and multiple resistance genes for aminoglycosides and quinolones. All MRSA were strong biofilm producers harboring the complete icaADBC and icaR operon. Seven CoNS isolates comprising five species (S. epidermidis, S. haemolyticus, S. sciuri, S. capitis and S. lugdunensis) were analyzed, with mecA gene detected in five isolates. S. haemolitycus (isolate 95), and S. lugdunensis were unable to form biofilm and did not harbor the complete icaADBCR operon. High variability of adhesion genes was detected, with atl, ebp, icaADBC operon, and IS256 being the most common. In conclusion, MRSA and CoNS isolates carrying genes for biofilm production, and resistance to β-lactam and aminoglycosides are associated with treatment failure in OIAIs.